Struggling With Aging and Illness: Life Experiences of Elderly Schizophrenia Patients in the Community of Taiwan (International Journal of Studies in Nursing, 2020)
Aims: The number of elderly patients with schizophrenia in Taiwan has increased significantly. Most Taiwanese patients with schizophrenia are community-dwelling and, if elderly, are at increased risk of mental illness and mental health problems. The life experiences of community-dwelling elderly patients dealing with schizophrenia in Taiwan have not been well studied. This study aimed to explore the lived experiences of such patients through in-depth interviews. Methods: This qualitative study was carried out in psychiatric hospital day-care centers in Taiwan. We interviewed 16 patients (9 men and 7 women, mean age=60.43 years, SD=5.53 years). Data were analyzed using Colaizzi’s method of analysis. Results: The five major themes pertaining to the life experiences of community-dwelling elderly schizophrenia patients were identified as: 1) living alone, feeling lonely, and caring for myself; 2) anxiety and pessimism about the future; 3) internal conflict and aging; 4) seeking help; 5) delaying needs and engaging in healthy activities. Conclusions: The community-dwelling elderly schizophrenia patients were worried about the deterioration of their health, loss of self-care ability with aging, and decreasing access to community support and resources while striving to maintain their lives in the community. Mental health care professionals should understand the needs and abilities of patients, and help them to continue to live in the community. In addition to accepting continuous treatment, the patients should be encouraged to maintain healthy behaviors as well as enhance functioning and quality of life.